STRATEGI PENGEMBANGAN OBYEK WISATA PANTAI BINASI DI KOTA PARIAMAN - Nur Difal Ikhsan; Syafri Anwar (JURUSAN GEOGRAFI FIS UNP, 2023)
ABTRACT Nur Difal Ikhsan. STRATEGI PENGEMBANGAN OBYEK WISATA PANTAI BINASI DI KOTA PARIAMAN. Skripsi, Padang: Fakultas Ilmu Sosial. Universitas Negeri Padang. 2021 This study aims to Knowing the development strategy of Binasi Beach tourism object in Kota Pariaman. This type of research is descriptive qualitative. This research is located in Marunggi village, Kec. South Pariaman. The informants in this study were the Head of Marunggi Village and Visitors. Data collection techniques in this study are interviews and observations. In this study, the data analysis technique used the SWOT analysis method. Binasi Beach is still undeveloped, but this object has the potential to develop, its beauty and panorama are able to attract tourists to feel the harmonious atmosphere of the beautiful and beautiful beach. Important factors in a tourist attraction consist of the presence of an attraction or object, the existence of facilities, the existence of a shopping center and cleanliness. The results of the research are in the form of a strategy for developing the Binasi Beach tourist attraction which is a new beach in a way that the manager must optimize the existing potential because in the future the manager plans to create new objects and new facilities for the development of tourism objects. Food buying and selling activities are expected to be concentrated in one location only. Threats that are known to be able to disrupt the comfort of visitors, these threats can be overcome with firmness from the manager because the threats that arise come from community behavior. waste managers can work together with other parties to maintain sustainability and also create new jobs.